Knowledge and Awareness of Detecting Oral Premalignant Lesions among Dental Students, Interns, and Practitioners in Saudi Arabia - Almutairi Farah; Alawad Abrar; Alshaya Yara; Alotaibi Yasser (Wolters Kluwer Medknow Publications, 2024)
Oral malignant lesions are the most common malignancy of which majority are diagnosed in advanced stages in Saudi Arabia. Patients with oral malignant lesion are first seen by general dental practitioners and dental students. Multiple surveys have been conducted and published to assess the students, interns, and dentists' awareness and attitude toward oral premalignant lesions worldwide. However, little is known about this issue in Saudi Arabia. We aimed to assess knowledge and awareness of detecting oral premalignant lesions among dental students, dental interns, and practitioners in Saudi Arabia. A cross-sectional questionnaire-based survey was conducted and electronically distributed. The questionnaire comprised of three sections including demographic variables, knowledge of risk factors of oral malignancy, and six clinical case scenarios. Descriptive statistics were used, and the results were reported using cross-tabulation and the Chi-square test. A 300 participants answered to the questionnaire, and 83% of respondents strongly agreed that smoking is a risk factor for oral malignancy. However, there was some uncertainty in responses for some more specific oral-related factors, such as a sharp-edged tooth and irritation from dental restoration. Furthermore, the knowledge and awareness of detecting frankly benign and frankly malignant lesions such as fibroma and squamous cell carcinoma are higher comparing to potentially malignant lesion, i.e. lichen planus. Knowledge and awareness of detecting oral premalignant lesions vary based on malignancy factors and by participants academic level. Fibroma and SCC are detected easily among all participants. However, lichen planus was the hardest to diagnose among oral lesions.